BLOCKCHAIN TECHNOLOGY IN MSME BOOKKEEPING IN INDONESIA - Mirna Amirya (Jurnal Ilmiah Akuntansi Peradaban, 2022)
Blockchain technology is experiencing rapid development in today's digital era. Likewise with MSMEs which show the growth of business actors and an increase in their contribution to the national economy (GDP) in Indonesia. The advantages offered by blockchain technology are expected to be able to support the business operations of a business entity, one of which is the bookkeeping of MSMEs in Indonesia. This study aims to analyse the potential application and use of blockchain technology in MSME bookkeeping in Indonesia. This study uses a qualitative method with a case study approach and analysis of explanatory strategies. The data used is secondary data. The results of the study found that blockchain can be used as a technology for MSME bookkeeping in Indonesia. One of the reasons is that all accounting transactions can potentially be tracked with the blockchain. The data in this technology can be considered as relevant information due to the nature of blockchain as a technology that records and stores data that cannot be changed and manipulated. Blockchain is used as a database and data processing is still carried out using an Accounting Information System. Blockchain cannot automatically process data into information that may be needed in accounting.